Process planning : the design/manufacture interface / Peter Scallan. - Scallan, Peter (Butterworth-Heinemann, 2002)
Peter Scallan takes the reader on a product's journey from the conception and design stage through to the finished item in this illustrated textbook. It provides everything needed to enable a student to prepare process plans for any given component.